Risk Factors of External Ventricular Drainage-Related Infections: A Retrospective Study of 147 Pediatric Post-tumor Resection Patients in a Single Center - Lu, Pengwei; Raynald,; Liu, Wei; Gong, Jian; Sun, Tao; Li, Chunde; Ma′ruf, Lukman; Fan, Yanzhu; Zhu, Ruifang; Tian, Yongji (Frontiers in Neurology, 2019)
Background: External ventricular drainage (EVD) is common after brain surgery. However, the incidence of EVD related infection (ERI) is still relatively high and can increase morbidity and mortality. Objective: The objective of this study was to analyze ERI factors in pediatric population post-brain tumor surgery. Methods: From January 2016 to December 2017, 147 patients less than 18 years old underwent tumor removal at Beijing Tiantan Hospital and had postoperative EVD. We recorded basic demographic data as well as several risk factors. We then analyzed whether these factors were related to ERI. Results: Patients with a preoperative ventriculo-peritoneal (V-P) shunt, longer operation time, received blood transfusion, more frequent cerebrospinal fluid (CSF) sampling, and longer indwelling time of EVD had higher risks of infection (P<0.05). Logistic regression analysis confirmed that a preoperative V-P shunt, operative duration, intraoperative blood transfusion, frequency of CSF sampling and EVD duration were correlated with postoperative ERI (P<0.05). Conclusion: EVD should be removed as soon as possible and any unnecessary procedures should be avoided to reduce the infection rate. However, prophylactic treatment should be given in cases of patients do not meet the indication for EVD removal.